Menavigasi Tantangan dan Peluang Pendidikan Multisektoral di Era Digital: Kajian Literatur Terkini - Amal Fathullah; Caroline Caroline; Diana Diana (FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2025)
This article presents a review of recent literature on the challenges and opportunities in implementing multisectoral education in the digital era. Digital transformation has great potential to transform global education systems to be more inclusive and personalised, despite challenges such as unequal access to technology and digital skills. The study highlights the importance of collaboration between sectors, including education and industry, to create relevant curricula that support labour market needs. Strategic partnerships and the utilisation of digital platforms and data-driven solutions can drive innovation in teaching and learning methods. To maximise this potential, a concerted effort from various stakeholders is required, including supportive policies, investment in technology infrastructure and continuous digital skills training. The results of this study are expected to provide guidance for stakeholders in developing education strategies that are adaptive and responsive to the digital era.